Hubert Damisch / Jean Dubuffet - Entrée en matière correspondance 1961-1985, textes 1961-2014 - Damisch, Hubert 1928-2017; Dubuffet, Jean 1901-1985 (JRP/Ringier, 2016)
French artist Jean Dubuffet and French art historian Hubert Damisch shared a long friendship between 1961—the year Damisch published his first essay on Dubuffet—and 1985—when the latter died. "Entrée en matière" gathers together all the texts written by Damisch on Dubuffet as well as a selection of their correspondence: one is able to follow how the thinking on a living artist could be inspired by a close relationship with him, but also by philosophy, human sciences, and other artists' oeuvres; and how in addition this thinking could evolve once the dialogue becomes a tribute monologue after the artist's death. Jean Dubuffet (1901–1985) is one of the main figures of postwar art, famous for his radical experimentation with form and material from the 1940s to the mid-1960s, his landmark bodies of later works such as "L’Hourloupe" (1962–1974) and "Coucou Bazar" (1973), his provocative thinking about high and low culture, and his advocacy for Art Brut artists. A philosopher specialized in aesthetics and art history, Hubert Damisch (b. 1928) is known for his essays on perspective, the theory of painting, and architecture. He edited the complete writings of Jean Dubuffet in four volumes between 1967 and 1985. Illustrated by Dubuffet' artworks and facsimiles of his correspondence, the volume is introduced and edited by art historian and curator Sophie Berrebi, a member of the editorial board of the academic journal "Stedelijk Studies," which publishes widely on contemporary art.
Includes bibliographical references
Keywords: Dubuffet, Jean -- 1901-1985; Damisch, Hubert -- 1928-2017; Art brut; Damisch, Hubert; Dubuffet, Jean; Briefsammlung; Anthologie